The Behaviour of Generation Z Towards the Use of Sharia Digital Banking: Perspectives of Trust, Financial Literacy, and Religious Values - Achmad Tarmidzi Anas (CV. Civiliza Publishing, 2025)
This study examines the behavioral intentions of Generation Z toward the use of Islamic digital banking services, emphasizing the roles of trust, Islamic financial literacy, and religiosity. Motivated by the growing yet underutilized potential of Gen Z in Indonesia's digital banking market, this research adopts a quantitative explanatory approach using Structural Equation Modeling – Partial Least Squares (SEM-PLS) to evaluate the causal relationships among the variables. The study surveyed Muslim individuals aged 18 to 27 who had experience using digital banking platforms. Data were collected through purposive sampling and analyzed using SmartPLS. The results indicate that all three independent variables have a significant and positive influence on the intention to use Islamic digital banking services. Among these, trust emerged as the most dominant predictor, suggesting that perceptions of system security, institutional transparency, and Shariah compliance greatly shape user decisions. Additionally, higher levels of Islamic financial literacy enhance rational financial behavior and product differentiation between conventional and Islamic banking. Religiosity also proved to be a meaningful determinant, reinforcing that spiritual values influence economic decisions even in a digital environment. This study contributes to the theoretical advancement of Islamic behavioral finance by integrating cognitive, affective, and normative dimensions into a unified framework. Furthermore, the findings provide practical insights for Islamic banking institutions in designing trust-based and value-aligned digital services targeted at Generation Z consumers. The research also recommends expanding the Technology Acceptance Model (TAM) by incorporating ethical-spiritual constructs to better contextualize financial behavior in Muslim societies.